(3QSGdI aj GdaQGFVs - (3GdWhSj, CHh LYaQ, fUjQ GdOjf, eMeO Hf eMeO Hf GdMSf, J (B672 (3g`s
(3ChdgG (B:s
...(3jUQM GdeGdc HGdfgj YfgG Ch JhLg Ydjg VQQ HGdUdGI ajgG , bhdg hJHWd HGdeZUhH hdh cGf (B.. (3eTGHgI GdMGd NdGaG ddeQjjV (B...s
(3BNQgG (B:s
.. (3EPG GOYj ehbY GdUfYI YOe GbJQGf GjbGYg HbUO eOdhdgG hXGgQ LeY ef GdCUMGH YOe SeGY OYhGg dYLe GecGf GbGeI GdHjfI YdjgG (B...(3eGde jbGQfg QVGgs
(3efbhdI Yf fSNI HNW GdeDdas
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdGYdGe (B7\30s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3abg GdePGgH GdCNQis